The Role of Customer Trust, Customer Perception, Customer Online Behavior, and E-Service Quality Towards Customer Preference on E-Market Place - Saaed Ahmed Saeed Alasrani; Ani Wulandari (Jurnal Ekonomi, 2022)
This study is aimed to analyze The Role of Customer Trust, Customer Perception, Customer Online Behavior, and E-Service Quality towards Customer Preference on E-Market Place in Surabaya City. This is an explanatory research using questionnaires. Population in this study is customers in Surabaya city who make purchases through e-commerce Platforms (Shopee, Tokopedia, Lazada). Samples of 100 customers are chosen by purposive sampling method. The Method analysis used in this study is multiple regression analysis with SPSS 21 software which was employed as a data management strategy. Research findings revealed that Customer Trust, Perception, Online Behavior and E-Service Quality each of them have a partial positive significant effect on Customer Preference. Customer Trust, Customer Perception, Customer Behavior, E-Service Quality, simultaneously have a positive significant effect on Customer Preference.